Pentahelix Kebijakan Pemerintah Dalam Pengembangan Wisata Gunung Bromo - Sucahyo, Imam; Mahmud, Moh; Ludin Fr, Jalal; Khumairoh, Isna Wardhatul; Astono, Tidar; Putri, Nur Adinda (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Mount Bromo is a priority destination appointed by the government to become a pilot tour for other tours. Of course it is very feasible to test how good government policies are in the tourism sector. With the application of the pertahelix concept as a theory to create sustainable tourism. This research uses descriptive qualitative meaning research that focuses on objects, subjects, populations and is supported by facts in the field so as to produce data that is descriptive in nature in research. and government participation with its policies. Government policies must be in accordance with the consensus of the people on Mount Bromo, the aim is to facilitate and not cause policy overlap, both policies from the central and regional governments and customary laws that apply in the field. Of course tourism is a series of manifestations carried out by the community to provide or channel their creativity by utilizing natural resources by integrating people's habits, so with that there is tourism. The pertahelix concept and its implementation must all be sustainable; starting from the components of academia, business, community and mass media. even if there is a component that is deemed to have failed, the Pertahelix concept will not produce good tourism